Perspectives on musical aesthetics - Rahn, John (New York W.W. Norton, 1994)
In this volume, editor John Rahn has assembled a fascinating collection of essays that focus on creating, performing, and thinking about music in today's world. The essays, drawn from the journal Perspectives of New Music, reflect a wide variety of artistic viewpoints and the latest critical perspectives - all from the creative point of view. Featured writers include composers Pierre Boulez, John Cage, Iannis Xenakis, Milton Babbitt, Benjamin Boretz, and J. K. Randall, as well as literary scholars Douglas Collins and Arthur Nestrovski, anthropologist Eric Gans, philosopher Michel Foucault, and poet Delmore Schwartz. The first section, "Aesthetic Theory, " critiques recent theoretical speculation about music's origins and function by such thinkers as Theodor Adorno and Rene Girard. In the sections that follow, the authors contemplate the changing relations between music and society, the effects that today's often conflicting aesthetic notions have on serious composition, the close relation between music and other forms of communicative behavior (including other art forms), and music as part of a larger consciousness. Taken together, the essays suggest a new working aesthetic that champions a synthesis between individual impulse and collective responsibility and aims to ensure that the artistic tradition remains alive in Western culture.A fascinating collection of essays on creating, performing, and thinking about music in today's world.Drawn from the influential journal Perspectives of New Music, these essays reflect a variety of artistic viewpoints and critical perspectives. The contributors include composers Pierre Boulez, John Cage, and Milton Babbitt, literary scholar Douglas Collins, anthropologist Eric Gans, philosopher Michel Foucault, and poet Delmore Schwartz. The authors contemplate music's origins and function, the changing relations between music and society, the effects of today's conflicting aesthetic notions on composition, and the relationship between music and other communicative behaviors. Taken together, the essays suggest a working aesthetic that would ensure the continual renewal of artistic tradition in Western culture.